Inflammatory demyelinating polyneuropathies and patient management during the COVID-19 pandemic. Literature review - Bunevičiūtė , R.; Klimašauskienė , A. (Neurologijos seminarai, 2020)
Inflammatory demyelinating polyneuropathies are rare but potentially treatable disorders. They can cause a lot of difficulties in daily practice due to their clinical heterogeneity and long term immunosuppressive treatment. Environmental and epidemiological changes may increase the incidence of the demyelinating polyneuropathies. This article considers the main clinical features, basics of diagnosis and treatment of acute and chronic inflammatory demyelinating polyneuropathies with a special attention to the management of patients during the COVID-19 pandemic.